Tratamentos alternativos e peliculização de sementes de milho para controle de Sitophilus zeamais - Portolan, Isis Bruna (2020)
Corn is one of the main cereals grown on the world, is the second most produced grain in the Brazilian territory and its seed is important not only for its annual production, but for the relationship with the Brazilian agricultural production. In small rural properties, corn seeds are usually stored after harvest for future sowing, however, such seeds are normally stored with low or no health control, presenting a high potential for infestation of pests, such as Sitophilus zeamais MOTS. Thus, the objective of this work was to evaluate the efficiency of pelliculation and different products of plant origin in the control of corn weevil (Sitophilus zeamais) and its influence on the physiological quality of corn seeds. For this purpose, this work was divided into two chapters. The experimental design used in the first chapter was completely randomized (DIC), in a bifactorial scheme, 5 x 4, with five vegetable derivatives (Piper nigrum, Pinnus elliottii, Ricinus communis, Corymbia citriodora and Cinnamomum zeylanicum) and four concentrations (0, 2, 4 and 6 g.kg-1 of seeds). The evaluations were carried out at two (zero time) and at thirty days (time 30), after seed treatment, with tests of humidity, germination, mortality and insect repellency. Black pepper was effective for the control of S. zeamais and its toxicity to insects is directly proportional to the increase in the concentration of application in corn seeds. Black pepper and castor bean have a repellent action against S. zeamais regardless of the storage time of the seeds and the concentration of the product used. Castor at a concentration of 4 g.kg-1 impairs the physiological quality of corn seeds. Chapter 2 evaluated the efficiency of pelliculation and different pepper powders in the repellency and control of corn weevil and its influence on the physiological quality of seeds during storage. The experimental design used was completely randomized, adopting the 5 x 4 x 2 three-factor scheme and an additional one. The treatments were Black Pepper (Piper nigrum L.), Cayenne Pepper (Capsicum annuum L.), Jamaica Pepper (Pimenta dioica L.), Lady's Finger Pepper (Capsicum baccatum L.) and control, four evaluation periods (0, 45, 90 and 135 days), with and without pelliculation and an additional treatment (chemical insecticide - Gastoxin® B57), with four repetitions. Bioassays were carried out to evaluate the physiological quality of seeds, infestation, repellency and insect mortality. The use of pelliculization impaired the insecticidal effect of vegetable powders, contributing to the increase of insect infestation and consequently reducing the physiological quality of seeds during storage. The treatments with black pepper and Lady’s finger peper, did not affect the physiological quality of the seeds during storage. The treatments that caused the highest mortality were black pepper and Jamaica pepper, without pelliculation. However, further studies on dosage, form of use and storage period are necessary.